The effects of different types of RAGT on balance function in stroke patients with low levels of independent walking in a convalescent rehabilitation hospital - Lee Dae-Hwan; Woo Bong-sik; Lim Jong-hyeon; Choi Jin-ook; Park Yong-Hwa (Open Medicine, 2025)
Stroke patients with low levels of walking independence often experience persistent deficits in gait and balance, which significantly limit their functional mobility and quality of life. Robotic-assist gait training (RAGT) has emerged as a promising intervention to promote motor recovery and improve postural control in this patients. While previous studies have demonstrated the benefits of RAGT, few have directly compared the effects of fixed end-effector type and mobile robotic gait devices in patients with severely impaired ambulation. This study aimed to investigate and compare the effects of these two robotic gait training on balance and lower extremities motor recovery in stroke patients classified as functional ambulation category 0 to 2.